A randomised trial of a brace for patellofemoral osteoarthritis targeting knee pain and bone marrow lesions. Issue 6 (16th January 2015) - Callaghan, Michael J; Parkes, Matthew J; Hutchinson, Charles E; Gait, Andrew D; Forsythe, Laura M; Marjanovic, Elizabeth J; Lunt, Mark; Felson, David T
Abstract : Objective: Braces used to treat (PF) osteoarthritis (OA) may reduce contact stress across the PF joint. We hypothesised that in PF OA, braces would decrease knee pain and shrink PF bone marrow lesions (BMLs). Methods: Eligible subjects had painful PF OA. Subjects were randomly allocated to brace or no brace for 6 weeks. Knee MRIs were acquired at baseline and 6 weeks. We measured BMLs on post-contrast fat suppressed sagittal and proton density weighted axial images. The primary symptom outcome was change in pain at 6 weeks during a preselected painful activity, and the primary structural outcome was BML volume change in the PF joint. Analyses used multiple linear regression. Results: We randomised 126 subjects aged 40–70 years (mean age 55.5 years; 72 females (57.1%)). Mean nominated visual analogue scale (0–10 cm) pain score at baseline was 6.5 cm. 94 knees (75%) had PF BMLs at baseline. Subjects wore the brace for a mean of 7.4 h/day. 6 subjects withdrew during the trial. After accounting for baseline values, the brace group had lower knee pain than the control group at 6 weeks (difference between groups −1.3 cm, 95% CI −2.0 to −0.7; p<0.001) and reduced PF BML volume (difference −490.6 mm 3, 95% CI −929.5 to −51.7; p=0.03) but not tibiofemoral volume (difference −53.9 mm 3, 95% CI −625.9 to 518.2; p=0.85). Conclusions: A PF brace reduces BML volume in the targeted compartment of the knee, and relieves knee pain. Trial registration number: UK. ISRCTN50380458 .